Decreased tubulin-binding cofactor B was involved in the formation disorder of nascent astrocyte processes by regulating microtubule plus-end growth through binding with end-binding proteins 1 and 3 after chronic alcohol exposure - Zheng, Yin; Yang, Mei; Chen, Xiaoqiao; Zhang, Gaoli; Wan, Shanshan; Zhang, Bingqiu; Huo, Jiechao; Liu, Hui (Frontiers in Cellular Neuroscience, 2022)
Fetal alcohol syndrome (FAS) is a neurological disease caused by excessive drinking during pregnancy and characterized by congenital abnormalities in the structure and function of the fetal brain. This study was proposed to provide new insights into the pathogenesis of FAS by revealing the possible mechanisms of alcohol-induced astrocyte injury. Firstly, a chronic alcohol exposure model of astrocytes was established and the formation disorder was found in astrocyte processes where tubulin-binding cofactor B (TBCB) was decreased or lost, accompanied by disorganized microtubules (MT). Secondly, to understand the relationship between TBCB reduction and the formation disorder of astrocyte processes, TBCB was silenced or overexpressed. It caused astrocyte processes to retract or lose after silencing, while the processes increased with expending basal part and obtuse tips after overexpressing. It confirmed that TBCB was one of the critical factors for the formation of astrocyte processes through regulating MT plus-end and provided a new view on the pathogenesis of FAS. Thirdly, to explore the mechanism of TBCB regulating MT plus-ends, we first proved end binding proteins 1 and 3 (EB1/3) were bound at MT plus-ends in astrocytes. Then through interference experiments, we found that both EB1 and EB3, which formed in heterodimers, were necessary to mediate TBCB binding to MT plus-ends and thus regulated the formation of astrocyte processes. Finally, the regulatory mechanism was studied and the ERK1/2 signaling pathway was found as one of the main pathways regulating TBCB expression in astrocytes after alcohol injury.